2020
DOI: 10.1001/jamanetworkopen.2020.11014
|View full text |Cite
|
Sign up to set email alerts
|

Use of Health Savings Accounts Among US Adults Enrolled in High-Deductible Health Plans

Abstract: IMPORTANCE Health savings accounts (HSAs) can be used by enrollees in high-deductible health plans (HDHPs) to save for health care expenses before taxes. Expansion of and encouraging contributions to HSAs have been centerpieces of recent federal legislation. Little is known about how US residents who may be eligible for HSAs are using them to save for health care. OBJECTIVE To determine which patients who may be eligible for an HSA do not have one and what decisions patients with HSAs make about contributing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Therefore, these findings may partly be due to employer contributions that decreased enrollee deductibles (23% of covered workers in an HSA-qualified HDHP receive employer contributions that reduce actual liability to <$1,000 when applied to deductibles). 10 Given that few adults with an HSA were able to afford healthcare savings in the last year, 34 studies investigating the differences by whether employers offer HDHPs with (and make contributions to) a health savings plan option are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these findings may partly be due to employer contributions that decreased enrollee deductibles (23% of covered workers in an HSA-qualified HDHP receive employer contributions that reduce actual liability to <$1,000 when applied to deductibles). 10 Given that few adults with an HSA were able to afford healthcare savings in the last year, 34 studies investigating the differences by whether employers offer HDHPs with (and make contributions to) a health savings plan option are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…HSA-eligible and HRA-eligible HDHP members with chronic diseases consistently had higher OOP and higher total costs than members in nonaccount based HDHPs (online supplemental appendix 7), possibly because the accounts provide funds that lower barriers to utilisation and reduce the effective OOP cost of care through use of pretax dollars. However, another study found that more than half of the members with HSAeligible HDHPs do not contribute money to their HSA, 24 suggesting that HSA accounts may not actually reduce the OOP burden for the majority of HDHP members. Our finding that members with chronic diseases paid OOP for a lower share of total costs than healthier members Open access is because members with chronic diseases have much higher total costs and many high costs members hit their deductible and OOP max limits.…”
Section: Total Costsmentioning
confidence: 99%
“…Kullgren and colleagues 1 found that higher-income respondents (ie, 250%-400% of the federal poverty level) were more likely to enroll in an HSA than lower-income respondents (<250% of the federal poverty level). 1 These enrollment differences may create a greater financial burden of out-of-pocket health care costs on lower-income families, but this study did not address that possibility. However, a recent study of low-income adults with multiple chronic conditions enrolled in employer-sponsored insurance found that almost half had a family out-ofpocket health care burden exceeding 20% of family disposable income, which was considerably higher than that of similar low-income adults in low-deductible or no-deductible plans.…”
mentioning
confidence: 91%
“…Employers and policy makers may be able to increase HSA enrollment and savings by making the benefits of HSA participation more transparent and understandable, because this study found that HSA enrollees in the highest tertile of health insurance literacy were more likely to contribute to their HSA than those in the lowest tertile. 1 Even greater improvements might be realized if employers leveraged the important insight from behavioral economics that default options strongly influence participation rates. 6 If HSA enrollment and a monthly contribution at a fixed amount or percentage of income were the default options that employees had to opt out of, future HDHP enrollees may not experience the same outcomes of those in the 2016 sample from this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation